2017
DOI: 10.5604/01.3001.0010.7004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different approaches to 3d numerical model development of the contact zone between elementary asperities and flat surface

Abstract: This paper presents two triaxial finite element (FE) models: a “full model” and a “quarter model”, representing the contact between the specimen’s rough surface and the ideally smooth and flat surface of the punch. Models have a contact zone that represents the topography of the real surface and has elastoplastic properties close to those of the real contact. The contact zone was entirely modelled on the basis of roughness measurements performed on a real milled specimen made of 5083 aluminium alloy. The devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Using the Cauchy-Riemann relations (43), one can show that the equations in (44) taken in parentheses are also equal to zero. This has already been shown in (19) To obtain the final solution to the continuity equation (33), it is necessary to show that functions I 1 and I 2 satisfy the Laplace equations (33) as well since they are part of the final result of (37) to (39). Substitute (35), (36) into (39) taking into account:…”
Section: Invariant Differential Generalizations In the Problemmentioning
confidence: 93%
See 1 more Smart Citation
“…Using the Cauchy-Riemann relations (43), one can show that the equations in (44) taken in parentheses are also equal to zero. This has already been shown in (19) To obtain the final solution to the continuity equation (33), it is necessary to show that functions I 1 and I 2 satisfy the Laplace equations (33) as well since they are part of the final result of (37) to (39). Substitute (35), (36) into (39) taking into account:…”
Section: Invariant Differential Generalizations In the Problemmentioning
confidence: 93%
“…Differential relations in the problem [18] were applied but they are inapplicable to the generalizations using argument functions. General approaches were considered in [19] where conditions of coupling in the sample-punch interaction were taken into account. The analysis has shown that they (conditions) do not adequately reflect the possibility of finding a concrete solution to the problem taking into account the application of the argument functions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Publication [14] examines the contact interaction between a sample and a punch. Common approaches to the problem were complemented by the relationship conditions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Operators in (14) that are adjacent to the exponents contain the same second derivatives for coordinates and non-linearity. If for some reason the operators are zero, then there is an identity.…”
Section: Solving the Problem From The Theory Of Elasticity Using The mentioning
confidence: 99%
See 1 more Smart Citation